Institutional analysis of strategic choice of micro, small, and medium enterprises a conceptual framework - Roxas, Hernan G.; Lindsay, Val; Ashill, Nicholas; Victorio, Antong (2007)
A conceptual framework is presented showing formal and informal institutions and their relationship with the strategic choice of micro, small and medium enterprises (MSMEs) in a developing-country setting. Emphasis is placed on how institutions at the subnational level (such as a region or city) influence the strategic orientations of MSMEs in the wake of decentralization, which grants subnational government authorities more political, economic, fiscal, and administrative powers. Furthermore, the paper sheds light on the environmental (institutional) determinism-organizational (strategic) choice nexus. It offers propositions, questions, and issues worth pursuing in future empirical investigations.
Title was 'Philippine Review of Business and Economics' until 1979. Title changed to 'Philippine Review of Economics and Business' from 1980-2000, and again changed to 'Philippine Review of Economics' since 2001.
Includes bibliographical references (pages 174-186).
Keywords: Small business -- Developing countries; Informal sector (Economics) -- Developing countries; Sale of small businesses